(untitled) (Sustainability in Debate, 2023)
The expansion of wind energy in Brazil has brought benefits, but many conflicts have arisen around rural communities. The research involved understanding the community’s responses regarding the acceptance or rejection of wind farms in the Serra dos Pereiros community in Piauí from the procedural and distributive justice view. A questionnaire with ten answers was applied, which added together 31 variables. In statical analyses, with a population sample of 69 people, the Likert scale, Cronbach’s alpha coefficient, and Spearman’s correlation coefficient (rs) were used. From the results, 5 responses presented moderate positive or strongly positive correlations: change in the landscape, opinion about wind farms, political process for implementing wind farms, fairness of the process, and compensation. The data show that the development of policies that do not include the direct participation of society generates conflicts between the different institutional levels and significant local environmental and social problems.